(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-142-152 The phonetics section is basic for mastering the system of both foreign and native languages. However, the study of phonetics causes significant difficulties due to the complexity of language material and insufficient theoretical and practical understanding. In this regard, the article proposes a number of areas of study and systematization of phonetic phenomena, including contributing to the diversity of the educational process and increasing the motivation of students in mastering the classification of phonemes and their positional changes. This approach requires the disclosure of the linguometodic potential of the study of phonetics and the strengthening of its practical orientation. Key words: Russian language, linguometodics, phonetics, phonetic organization, syntagmatic laws, orthoepia, homophony, principles of Russian spelling, motivation